2022
DOI: 10.1155/2022/1924906
|View full text |Cite
|
Sign up to set email alerts
|

Survival Prediction Model for Patients with Esophageal Squamous Cell Carcinoma Based on the Parameter-Optimized Deep Belief Network Using the Improved Archimedes Optimization Algorithm

Abstract: Esophageal squamous cell carcinoma (ESCC) is one of the highest incidence and mortality cancers in the world. An effective survival prediction model can improve the quality of patients’ survival. Therefore, a parameter-optimized deep belief network based on the improved Archimedes optimization algorithm is proposed in this paper for the survival prediction of patients with ESCC. Firstly, a combination of features significantly associated with the survival of patients is found by the minimum redundancy and maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…Parameter adjustments aim to achieve the best accuracy and reduce the time and cost of model training. As shown in Figure 5, this study statistically analyzed hyperparameter optimization, and the results were consistent with the conclusion of Wang et al [44], who found that the learning rate and batch size were the two most essential hyperparameters. Parameter adjustments aim to achieve the best accuracy and reduce the time and cost of model training.…”
Section: Hyperparameter Tuningsupporting
confidence: 89%
See 3 more Smart Citations
“…Parameter adjustments aim to achieve the best accuracy and reduce the time and cost of model training. As shown in Figure 5, this study statistically analyzed hyperparameter optimization, and the results were consistent with the conclusion of Wang et al [44], who found that the learning rate and batch size were the two most essential hyperparameters. Parameter adjustments aim to achieve the best accuracy and reduce the time and cost of model training.…”
Section: Hyperparameter Tuningsupporting
confidence: 89%
“…Supplementing average value [16,17], linear interpolation [17,18], KNN [19,20] Dimensionality reduction PCA [8], pooling layer [21], t-SNE [22], SPCA [23] Removing outliers Pauta criterion [18], EWMA [24] Feature selection PSO [1], LASSO [8,25], ASO [26], GA [27], MI [28], GRA [29], PCC [30], CCA [31] Decomposition EMD [32], EEMD [33], CEEMDAN [19,27,[34][35][36][37][38], ICEEMDAN [39], SSA [40,41], VMD [42], SVMD [43] Normalization [6,17,20,27,30,31,34,42,[44][45][46][47][48][49]…”
Section: Missing Valuesmentioning
confidence: 99%
See 2 more Smart Citations
“…The predicted AUCs for 1-year, 3-year, and 5-year survivals were 0.851, 0.806, and 0.793, respectively. Wang et al 25 proposed a novel DL network IAOA-DBN combining DBN and Archimedean optimization algorithm for predicting the 5-year survival of patients with esophageal squamous cell carcinoma. First, a minimum redundancy maximum correlation algorithm was used to screen statistically significant features.…”
Section: Progress Of DL In Cancer Prognosis Predictionmentioning
confidence: 99%